A COORDENAÇÃO PEDAGÓGICA NO ENSINO MÉDIO: ACOMPANHAR O TRABALHO PEDAGÓGICO OU APAGAR INCÊNDIOS? - Santos, Sílvia Cristina Pantano dos (2008)
The present study it makes an inquiry on the attribution to form professors during the Time of Collective Pedagogical Work (HTPC), that the coordinating professors of the São Paulo state net had received with the implantation from the program Ensino Médio em Rede, in the period of 2004 the 2006. The study it provides an analysis of the condition of formation of these educators, from its professional trajectories, focusing the construction of its identity and looking for to find the common elements gifts in the passage of each one, as well as the difficulties lived deeply in the development of this work and the strategies and alternatives adopted for them to surpass them. Beyond the consultations the diverse theoretical and legal references, the research happened through work of systemize field to break of questionnaires and interviews with coordinating professors. In what it is mentioned to the analysis of the professional trajectories of the coordinating professors, the theoretical recital counted on the contributions of Antonio Nóvoa, Christine Josso and Zeila de Brito Fabri Demartini. Michel de Certeau subsidized the reflections on the used mechanisms stops to cheat the politics of formation in mass imposed to all the schools of Average Education of the State of São Paulo.(AU)